Analisis Dampak Pendaftaran Tanah Sistematis Lengkap terhadap Sektor Investasi Properti di Wilayah Kota Medan - Fadhila Putri Kaban; Yusrizal Yusrizal (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This study analyzes the impact of the implementation of the Complete Systematic Land Registration (PTSL) Program on the property investment sector in Medan City. The PTSL program aims to provide legal certainty over land ownership rights, which leads to an increase in property value and attracts investors. This research employs a qualitative approach through direct observation during an internship at the Medan City Land Office. The findings indicate that PTSL positively contributes to the growth of property investments by enhancing legal certainty, improving bureaucratic efficiency, and increasing regional tax revenues. However, challenges such as low public awareness and limited human resources remain. Therefore, more intensive public outreach and improved staff competence are necessary to optimize the program’s implementation.